Leucoagaricus cupresseoides (Agaricaceae), a new species in sect. Piloselli and L. aurantiovergens and L. pseudopilatianus redescribed from Italy - Forin, Niccolò; Tatti, Alessia; Vizzini, Alfredo; Coppola, Alessandra; Migliozzi, Vincenzo (Phytotaxa, 2022)
A new species, Leucoagaricus cupresseoides, from a pine forest in Castelfusano, Rome, Italy, is described based on both morphological and molecular analyses. Updated morphological descriptions of Leucoagaricus aurantiovergens and L. pseudopilatianus are presented due to new collections from Italy and confirmed by nrITS sequence analysis of the type specimens of the two species. Based on our morphological and molecular analyses, L. pseudopilatianus var. roseodiffractus and L. paracupresseus are synonyms of L. aurantiovergens; and L. pseudopilatianus var. rugosoreticulatus is not molecularly distinct from L. pseudopilatianus. Leucoagaricus cupresseus, L. cupresseoides, L. aurantiovergens and L. pseudopilatianus form the L. cupresseus complex for which a comparative table is provided.